Employees Work Stress Level in the Hospital - Syaebani, Muhammad Irfan; Puteri, Lolyta Aditya (International Research Journal of Business Studies, 2018)
Workers in the health industry are more likely having a higher level of stress compare to other professions in other sectors. Work stress impacts adverse consequences such as fatigue, absenteeism, turnover, customer dissatisfaction, and for health professionals, in particular, it will lead to incorrect diagnosis and curative action. The study aims to identify the source of stress in the hospital among three divisions; medical professional, medical support, and general support as a case study to 181 employees at a hospital in Depok city. Job stress survey (JSS) is selected to measure employee work stress based on three indicators: job stress, job pressure, and lack of organisational support. Job stress survey maps the severity of stress, the frequency of stress, and the index of stress for all those three indicators. The research design is quantitative and uses analysis of variance (ANOVA) to test the different level of stress among three divisions. The result indicates the level of stress is different among three divisions based on stress severity. However, the difference is insignificant on stress frequency and stress index on two indicators namely job pressure and lack of organisational support. Among three divisions, professional medical workers experience the highest level of stress. The implication of the research is discussed.